The origin and transfer of water and solutes in peatlands: A multi tracer assessment in the carbonated Jura Mountains. Issue 12 (26th December 2022) - Lhosmot, Alexandre; Bouchez, Julien; Steinmann, Marc; Lavastre, Véronique; Bichet, Vincent; Loup, Christophe; Stefani, Vanessa; Boetsch, Anne; Chevet, June; Toussaint, Marie‐Laure; Gaillardet, Jérôme; Bertrand, Guillaume
Abstract: Peatlands provide a large panel of socio‐ecosystemic services such as biodiversity, water and carbon storage and amenities. Hydrological and geochemical interactions between peats and their surroundings are expected to be favoured in mountainous areas, which are nowadays increasingly sensitive to climate changes. In order to provide an integrated scheme of potential interactions, this study evaluates spatio‐temporal patterns of environmental tracers ( 87 Sr/ 86 Sr, δ 18 O/δ 2 H, elemental ratios) during high‐ and low‐flow periods in the largest peatland complex of the Jura Mountains (France). Systematically depleted δ 18 O/δ 2 H values in the deepest peat pore waters suggest contrasted dynamics and origins, both compatible with either preferential winter recharge or supply from adjacent high‐elevation areas. Combined with strontium isotopes ( 87 Sr/ 86 Sr), we show that these water fluxes are purveyors of solutes derived from water‐rock interactions, modified by mixing, evapotranspiration and dilution with local meteoric inputs. An end member mixing analysis of the peat pore water solute composition is consistent with a major contribution of carbonates from the regional Cretaceous limestone formations, located beneath fluvio‐glacial Quaternary deposits underlying the peat. This contribution implies a significant upward water flux from the underlying syncline that could reach a sufficient hydraulic head thanks to recharge from an adjacent regional anticline. These multiscale (anticline‐syncline, syncline‐peatland, peatland‐surface) constraints allow us to propose a relevant scheme for the hydrogeochemical functioning of the peatland, enabling an improved understanding of the current high socio‐ecosystemic value of the area, and the potential future evolution of the related services. Abstract : This work illustrates the interest of combining geochemical approaches to clarify complex patterns of water and solutes supplies of temperate peatlands in carbonated environments. The proposed multiscale functioning provide perspectives about the evolution of watershed‐peatland interactions which constrain current and future socio ecosystemic services.